'Patti Smith, Bloomsbury, and the Afterlives of Modernist Objects'. Issue 2 (May 2022) - Garrity, Jane
Abstract : This essay focuses on the photographs of Patti Smith that were shown at the Dulwich Picture Gallery's exhibition titled 'Legacy: Photographs by Vanessa Bell and Patti Smith' (London, February 8 to June 4, 2017). It tracks the parallel resonances between Smith and Bloomsbury with respect to ideas concerning the inseparability of materiality, emotion, and the body. The essay argues that Smith's photographs of 'Bloomsbury objects' convey that the immaterial can only be expressed through the material, a paradox that is key to understanding how such objects function as spiritualized relics that both highlight and supersede the dominion of the everyday.